The improvement of agronomic performances in the cold weather conditions for perennial wheatgrass by crossing Thinopyrum intermedium with wheat-Th. intermedium partial amphiploids - Liu, Yizhuo; Song, Weiwei; Song, Anning; Wu, Chunfei; Ding, Jiarui; Yu, Xiaoning; Song, Jia; Liu, Miaomiao; Yang, Xinyuan; Jiang, Changtong; Zhao, Haibin; Song, Weifu; et al. (Frontiers in Plant Science, 2023)
Thinopyrum intermedium (2n=6x=42, StStJ r J r J vs J vs ) is resistant or tolerant to biotic and abiotic stresses, making it suitable for developing perennial crops and forage. Through 5 cycles of selection, we developed 24 perennial wheatgrass lines, designated 19HSC-Q and 20HSC-Z, by crossing wheat-Th. intermedium partial amphiploids with Th. intermedium. The cold resistance, morphological performance, chromosome composition, and yield components of these perennial lines were investigated from 2019 to 2022. Six lines of 19HSC-Q had higher thousand-kernel weight, grains per spike, and tiller number than Th. intermedium, as well as surviving -30 ℃ in winter. Lines 19HSC-Q14, 19HSC-Q18, and 19HSC-Q20 had the best performances for grain number per spike and thousand-kernel weight. The 20HSC-Z lines, 20HSC-Z1, 20HSC-Z2, and 20HSC-Z3, were able to survive in the cold winter in Harbin and had been grown for two years. Sequential multicolor GISH analysis revealed that the J vs -subgenome of Th. intermedium were divided into two karyotypes, 3 pairs of type-I J vs chromosomes and 4 pairs of type-II J vs chromosomes. Both Th. intermedium and the 24 advanced perennial wheatgrass lines had the similar chromosome compositions, but the translocations among subgenome chromosomes were detected in some lines with prominent comprehensive agronomic traits, such as 19HSC-Q11, 19HSC-Q14, 19HSC-Q18, 19HSC-Q20 and the three 20HSC-Z lines. The chromosome aberrations were distinguished into two types: the large fragment translocation with St-J r , J vs -St, J r -IIJ vs , and J vs -J r and the small fragment introgression of J r -St, St-IJ vs and J vs -J r . These chromosomal variations can be used to further analyze the relationship between the subgenomes and phenotypes of Th. intermedium. Results of this study provide valuable materials for the next selection cycle of cold resistant perennial wheatgrass.